Artificial Intelligence (AI) Literacy and Academic Performance of Tertiary Level Students: A Preliminary Analysis - R. Asio, John Mark (Universitas PGRI Madiun, 2024)
This study intends to analyze the level of AI literacy among college students and its relationship to their academic performance. This investigation used a cross-sectional research design to address the research objective of the study. Eight hundred sixty-nine (869) college students served as participants in the investigation using an adapted instrument to measure AI literacy. Data from the respondents underwent statistical analysis, such as frequency, percentage, mean, independent t-test, Analysis of Variance, and Pearson-r Moment of Correlation. Results show that college students have a moderately high AI literacy level, and their academic performance was also highly satisfactory. The study also found significant differences in AI literacy in terms of college and gender and academic performance in terms of college, year level, and age. As for the relationship, there was a weak positive relationship between AI literacy and the academic performance of college students